2013
DOI: 10.1073/pnas.1310247110
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Darwin's conundrum reveals a twist on the relationship between phylogenetic distance and invasibility

Abstract: A key goal of invasion biology is to identify the factors that favor species invasions. One potential indicator of invasiveness is the phylogenetic distance between a nonnative species and species in the recipient community. However, predicting invasiveness using phylogenetic information relies on an untested assumption: that both biotic resistance and facilitation weaken with increasing phylogenetic distance. We test the validity of this key assumption using a mathematical model in which a novel species is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 49 publications
2
23
1
1
Order By: Relevance
“…A hypothesis opposed to DNH is related with preadaptation [29], [42][43], which proposes that phylogenetic closeness promotes the colonization process through facilitation among related taxa [41]–[42], [44][45]. Our results do not support this hypothesis, because colonization by Lactuca did not show a positive association with the phylogenetic relatedness of the assemblages.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…A hypothesis opposed to DNH is related with preadaptation [29], [42][43], which proposes that phylogenetic closeness promotes the colonization process through facilitation among related taxa [41]–[42], [44][45]. Our results do not support this hypothesis, because colonization by Lactuca did not show a positive association with the phylogenetic relatedness of the assemblages.…”
Section: Discussioncontrasting
confidence: 89%
“…Our results suggest that under the spatial scale used there was a null effect of the phylogenetic distance on colonization success and the invasion’s contingent conditions such as the current properties of resident assemblage, and the intrinsic properties of invaders would be more relevant in determining colonization success than factors associated with phylogenetic relatedness, as has been discussed by other authors [10], [41], [43], [46], [47]. This does not mean that phylogenetic distance between invader and resident assemblage does not affect the colonization process.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In contrast, most studies exploring the effects of phylogenetic relatedness between invasives and natives on community resistance (i.e. phylogenetic species‐based indices) have yielded mixed (Jones et al , Liu et al , Poe , Lososová et al , Marx et al ) or non‐significant results (Castro et al , Fleming et al ). Nevertheless, a recent study by Tan et al () in a manipulative experiment with bacterial assemblages found evidence that phylogenetic relatedness to invaders was a better predictor of biotic resistance than the phylogenetic diversity of the community.…”
Section: ) Which Communities Are More Resistant To Invasion?mentioning
confidence: 99%
“…Secondly, successful invaders might be expected to be more closely related to the native species pool because they share traits that pre-adapt them to the new environmental conditions in which they find themselves. Tests of Darwin's naturalization hypotheses have been mixed, and opposing predictions and mechanisms have been proposed (see Table 1 in Jones, Nuismer & Gomulkiewicz 2013). For example, there has been both documented evidence for increased susceptibility to attack by natural enemies (Hill & Kotanen 2009; Ness, Rollinson & Whitney 2011) and increased mutualisms (Richardson et al 2000b) among non-natives closely related to the native species pool.…”
Section: Discussionmentioning
confidence: 99%